The study of crack damage and fracture strength for single crystal silicon wafers sawn by fixed diamond wire. (1st November 2021) - Liu, Tengyun; Ge, Peiqi; Bi, Wenbo; Gao, Yufei
Abstract: Reducing the thickness of monocrystalline silicon wafers is an important measure to reduce the processing cost. The crack damage reduces the mechanical properties of silicon wafers and that has been a key restraining factor of wafer thinning. This paper uses the cross-section scanning microscopy method and three-point bending method to study the crack damage and fracture strength of wafers respectively. The median crack does not extend vertically downwards, but has a certain inclination angle. In addition, part of lateral cracks did not fully extend to the sliced surface and some of them are interlaced each other. The median crack and the lateral crack together form the subsurface crack damage. Most of the subsurface cracks have a depth between 5 μm and 13 μm, and the number of subsurface cracks with a depth between 7 μm and 9 μm is the largest. The number of cracks first increases and then decreases with the increase of subsurface crack depth. The fitted subsurface crack depth distribution function can better reflect the crack depth distribution characteristic. The direction of the surface cracks on the surface of the wafer is relatively complicated. The cracks have a certain angle with the groove, but the cracks show a certain regular distribution on both sides of the groove along the wire direction. The adjacent surface cracks cross each other to form more complex surface cracks. The fracture strengths of wafers are distributed between 70 MPa and 200 MPa. The larger the crack length, the overall Weibull distribution of fracture strength is biased to the left.